Broken stone with three vertical sections depicting different motifs - Temples of India Project Team (Jio Institute, 2024)
A small shrine, possibly a newer construction, is placed off-centred to the right facing the garbhagriha. Further steps lead to the third level, on a projected platform. Pieces from the temple have been repurposed in this shrine. The stone is broken and has three vertical sections. The section on the left has a purna kalasha (overflowing pot of prosperity) motif on the upper half and a makara (hybrid sea creature) inside a circular medallion at the bottom half. The mid-section has an intricate carving of kalpa vrisksha (tree of life) motif with figures of birds and kinnaras (hybrid human-bird creatures) camouflaged within the foliage. The section on the right has a purna kalasha motif on the top half and an eight-petal lotus blooming inside a circular medallion at the bottom half.